State-of-Charge Evaluation for Real-Time Monitoring and Evaluation of Lithium-Ion Battery Performance - Aye Aye Mon; Swe, Wunna (The Indonesian Journal of Computer Science, 2024)
Nowadays, lithium-ion batteries have been garnered significant attention as the primary energy source for energy storage devices within the renewable energy sector. Key concerns surrounding the utilization of lithium-ion batteries include ensuring satisfactory design lifespan and safe operation. Consequently, there's been a practical need for battery management. Responding to this demand, various battery state indicators have seen widespread implementation. Among the battery state indicators, accurate state-of-charge (SOC) estimation is an essential requirement for many situations where Li-Ion batteries (LiBs) are used. The effectiveness of a Battery Management System (BMS) safeguards the battery against deep discharging and over-charging to maximize its lifespan. This paper conducts state of charge (SOC) evaluation of a Li-ion battery module (12V, 13 Ah lithium titanate oxide (LTO) battery) for battery management systems (BMS) in energy storage systems (ESSs).